Studi Kelayakan Usaha Ternak Ayam Broiler Pada Pola Mandiri Dan Pola Kemitraan di Kabupaten Klaten - Ahmad Fauzi; Ratna Dewi Lestari (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2023)
This study aims to determine the feasibility of broiler chicken farming in partnership and independent patterns in Klaten Regency. The research method used is descriptive analysis. The samples used were determined deliberately. Analysis methods include revenue, costs, profits, B/C ratio indicators, R/C ratio, and Performance Index. Primary and secondary data were used in this research. The research results show that acceptance of the partnership pattern has an average of IDR 73,661,548 greater than the independent pattern. The average profit and total profit received by partnership breeders is much greater than that of independent breeders, amounting to IDR 28,004,337. The B/C ratio of the independent pattern broiler chicken farming business is 0.61 for the partnership pattern, while for the independent pattern, it is -0.15. The partnership pattern is more worth pursuing than the independent pattern as seen from the R/C ratio value where the partnership pattern is 1.61 while the independent pattern is 0.97 which is not worth pursuing. The environmental and legal aspects of the partnership pattern are feasible in the legal aspect, while the environmental aspect is not yet feasible because air pollution still occurs and the large number of flies that arise due to unprocessed chicken manure.